2019
DOI: 10.1088/1757-899x/547/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenolic Resin on Density, Porosity, Hardness, Thermal Stability, and Friction Performance as A Binder in Non-Asbestos Organic Brake Pad

Abstract: Phenolic resin is the most common resin binder used in brake pad materials. Selection of the relative amount of phenolic resin is an important to maintain structurally intact with the other ingredients of brake pad composite. In this experimental study, the effects of phenolic resin as a binder in non-asbestos organic brake pad was investigated. The brake pad composite was made using a powder metallurgy technique. Four formulations with different volume fractions 10, 15, 20, and 25 were selected. Parameters ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…With an increase in the volume percentage of phenolic resin, the friction coefficient will decrease, and the volume wear rate will rise. Moreover, while having superior thermal stability than the other specimens, composite samples comprising 10% and 15% phenolic resins were not recommended for use in the production of this brake pad since they have a poorer resistance to mechanical stress throughout friction performance tests [ 83 ].…”
Section: Factors Affecting the Performance Of Brake Padmentioning
confidence: 99%
“…With an increase in the volume percentage of phenolic resin, the friction coefficient will decrease, and the volume wear rate will rise. Moreover, while having superior thermal stability than the other specimens, composite samples comprising 10% and 15% phenolic resins were not recommended for use in the production of this brake pad since they have a poorer resistance to mechanical stress throughout friction performance tests [ 83 ].…”
Section: Factors Affecting the Performance Of Brake Padmentioning
confidence: 99%
“…At this stage, weight loss can be attributed mainly to the separation of water and gas from organic ingredients. 28 In the second range, weight loss in the temperature range of 300–650°C was in the ∼21–30%. Weight loss was specifically high in the 2nd range for all compositions.…”
Section: Resultsmentioning
confidence: 94%
“…It was also reported that phenolic resin can reduce porosity due to resin ran during the hot molding process and increase hardness. Nawangsari et al (2019) also concluded that higher content of phenolic resin can decrease the friction coefficient and increase the wear rate as well. In that work, the weakening of frictional performance with increasing phenolic resin was also explained by decreasing thermal stability.…”
Section: Introductionmentioning
confidence: 93%
“…Thermo-mechanical properties of the binder define the whole fade and recovery performance of the brake pad. Phenolic resin is one of the most common materials as a binder in friction material production thanks to its mechanical strength, chemical and heat resistance properties (Nawangsari et al , 2019). Consequently, several experimental works have been devoted to study its role in the brake pad materials.…”
Section: Introductionmentioning
confidence: 99%